Speaking Against Inequity in the Writing Classroom: Challenging the Performance Paradigm for Undergraduate Oral Presentations - Luger, Moberley; Stensrud, Craig (Discourse and Writing/Rédactologie, 2022)
Many undergraduate students continue to think of oral presentations as performances for an audience rather than dialogic exchanges of research. This focus on the aesthetics of performance, often promoted by speaking pedagogies in Canadian universities, can exacerbate classroom inequities by valuing certain ways of speaking and, by extension, certain speakers: speaking pedagogies, for example, that instruct students to speak “clearly,” dress “professionally,” or even to appear “confident,” can encode prejudices that privilege some voices and bodies over others, perpetuating discrimination based on gender, race, sexuality, language, ability, and culture. This article argues that an equitable scholarly speaking pedagogy needs to shift student thinking about academic oral presentations away from a focus on aesthetics and toward a view of scholarly speaking as part of a collaborative research process. The writing classroom, where similar changes have occurred in how we teach academic writing, is the best place to change students thinking about scholarly speaking. Drawing on genre-theoretical approaches to academic writing, we argue that this shift can be achieved by using “precedents”—recorded examples of scholarly speaking—to familiarize students with academic oral discourse’s genre conventions, helping students to recognize scholarly speaking as situated and dialogic. The article introduces a web resource, created by the authors, that uses precedents to encourage students and instructors to understand academic oral presentations as opportunities for cooperative research structured by shared discursive norms. Moreover, the site empowers students to challenge these norms, which might themselves encode biases. Ultimately, the site and the pedagogy that informs it not only challenge student prejudices about who can be a “good” speaker, but also remind students of their responsibilities—as speakers and audience members—to contribute to building an equitable classroom and university environment.